Low-cost preparation method of lithium iron manganese phosphate serving as anode material of lithium ion battery

By introducing a new process for preparing lithium manganese iron phosphate materials, the problems of low electronic conductivity and high cost of existing lithium manganese iron phosphate materials have been solved, realizing the preparation of high-performance and low-cost lithium-ion battery cathode materials.

CN121341980APending Publication Date: 2026-01-16CENT SOUTH UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511609221.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-05
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

Existing lithium manganese iron phosphate materials suffer from low electronic conductivity, poor Li+ diffusion ability, complex synthesis process, and high cost, which affect their application in lithium-ion batteries.

Method used

Manganese phosphate salts were prepared by reacting manganese oxides with phosphoric acid and hydrogen peroxide. Iron source and carboxylic acid carbon source were added, and after uniform mixing, lithium phosphate and organic carbon source were added. After spray drying and high-temperature sintering, high-performance lithium manganese iron phosphate cathode material was prepared.

Benefits of technology

It reduces preparation costs, improves the fluidity and uniformity of the slurry, enhances electrochemical performance, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121341980A_ABST
    Figure CN121341980A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium ion battery positive electrode materials, and particularly relates to a low-cost preparation method of a lithium ion battery positive electrode material lithium manganese iron phosphate. The preparation method comprises the following steps: firstly, reacting manganese oxide with phosphoric acid and hydrogen peroxide in advance to obtain manganese phosphate slurry; adding an iron source and a carboxylic acid-based carbon source into the reaction system, uniformly stirring and mixing, ball-milling for a period of time, adding lithium phosphate and an organic carbon source into the reaction container, fully and uniformly mixing the raw materials, and refining particles; and finally, carrying out spray drying and high-temperature sintering on the obtained slurry to prepare the lithium iron manganese phosphate positive electrode material. The method has the advantages of low slurry viscosity in the preparation process, high solid content, simple preparation process, low cost, easiness in batch and large-scale expansion and the like, and the prepared lithium manganese iron phosphate positive electrode material product has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of lithium ion batteries, in particular to a low-cost preparation method of a lithium manganese iron phosphate positive electrode material of a lithium ion battery. BACKGROUND

[0002] Lithium ion batteries are widely used in electric vehicles, energy storage power stations and portable electronic devices due to their high energy density, long cycle life and environmental friendliness. Among them, the positive electrode material is a key factor affecting the performance and cost of lithium ion batteries. At present, the most mature commercial application of lithium iron phosphate (LiFePO4, LFP for short) has the advantages of high thermal stability, good safety and long cycle life, but its energy density is relatively low, which has gradually been difficult to meet the demand for high energy density of power batteries and energy storage devices.

[0003] In order to improve the energy density of the battery, researchers have developed lithium manganese iron phosphate (LiMn x Fe 1-x PO4, LMFP for short) positive electrode material by partially doping Mn elements in LFP. LMFP not only inherits the excellent safety and cycle stability of LFP, but also improves the voltage platform through the redox reaction of the introduced Mn 2+ / Mn 3+ , thereby effectively improving the energy density of the battery. However, LMFP material still has the following problems: firstly, the intrinsic low electronic conductivity and poor Li + diffusion capacity of LMFP lead to limited rate performance; secondly, the synthesis process is complex, and traditional solid-phase method often has problems such as uneven reaction, particle agglomeration, high slurry viscosity and the like, which affect the consistency and controllability of the material; in addition, the synthesis cost is relatively high, and some preparation methods need to use high-priced raw materials or complex precursor synthesis routes, which limits its large-scale application.

[0004] Therefore, it is of great significance to develop a LMFP preparation method with simple process, low cost and excellent electrochemical performance to promote its application in lithium ion batteries. The application proposed in the application uses lithium phosphate as a lithium source, preforms manganese phosphate through a “manganese oxide-phosphoric acid-hydrogen peroxide” reaction, then introduces an iron source, a carboxylic acid-based carbon source, lithium phosphate and a second carbon source, and finally obtains a LMFP positive electrode material with excellent electrochemical performance through a process route of “mechanical activation-spray drying-high temperature sintering”. SUMMARY

[0005] The application aims to provide a preparation method of lithium manganese iron phosphate which is simple in process route and suitable for large-scale production.

[0006] The first object of the present application is to provide a simple route, convenient operation and large-scale production of lithium manganese iron phosphate synthesis preparation technology, aiming to improve the uniformity and batch stability of the product.

[0007] The second object of the present application is to provide a technical method for preparing lithium manganese iron phosphate by replacing lithium carbonate with lithium phosphate, which can reduce the production cost of raw materials, reduce the slurry viscosity of the reaction system, improve the fluidity of the slurry, improve the solid content, reduce the energy consumption of spray drying, improve the uniformity of element distribution, and obtain high-performance lithium manganese iron phosphate / carbon material.

[0008] To achieve the above technical purpose, the present application provides the following technical scheme: A low-cost preparation method of lithium ion battery cathode material lithium manganese iron phosphate, which adopts manganese oxide to react with phosphoric acid and hydrogen peroxide to obtain manganese phosphate slurry; then iron source and carboxyl carbon source are added to the reaction system, stirred and mixed uniformly, then ball milled for a period of time, then lithium phosphate and organic carbon source are added to the reaction container, and the raw materials are fully mixed and refined; finally, the obtained slurry is spray dried and high-temperature sintered to obtain lithium manganese iron phosphate cathode material, including the following steps: Step (1): a certain amount of manganese oxide and deionized water are weighed and added to the reaction container and stirred to obtain a uniform slurry; Step (2): a certain amount of phosphoric acid and hydrogen peroxide are weighed and mixed uniformly, pumped into the slurry of step (1) at a certain temperature, and stirred for a certain time; the reacted slurry is transferred to a ball mill tank for further ball milling for a certain time to obtain manganese phosphate slurry; Step (3): a certain amount of iron source is added to the slurry obtained in step (2), stirred uniformly, then carboxyl carbon source is added and reacted for a certain time; continue to ball mill for a certain time to ensure uniform reaction of the slurry; Step (4): the slurry obtained in step (3) is mixed with a certain proportion of lithium phosphate and a second carbon source, fully ball milled and sand milled, then spray dried to obtain lithium manganese iron phosphate precursor; the precursor is sintered at a specific atmosphere and temperature for a certain time to obtain lithium manganese iron phosphate cathode material with excellent performance; Step (5): the lithium manganese iron phosphate cathode material obtained in step (4) is mixed with a certain amount of conductive agent and binder to form a uniform slurry with N-methyl pyrrolidone as the solvent, and then coated on an aluminum foil and dried in a 120℃ vacuum oven; the obtained electrode piece is punched into a 14mm round piece, assembled into a button-type half-cell in an inert atmosphere glove box, and used for electrochemical performance test.

[0009] Preferably, the manganese oxide in step (1) is at least one of trimanganese tetraoxide, manganese dioxide and manganous oxide; the mass of deionized water is 1-5 times the mass of manganese source.

[0010] Preferably, the phosphoric acid concentration in step (2) is 60% to 85%, the molar amount of the phosphoric acid is (the total molar amount of transition metal ions minus the molar amount of phosphorus in the lithium source); the concentration of the hydrogen peroxide is 25% to 35%, the molar amount of the hydrogen peroxide is 1.2 to 2 times the molar amount of manganese ions in the theoretical reduced manganese source; the reaction time is 0.2 to 1 h; in the ball milling reaction, the ball milling speed is 300 to 500 r / min, and the ball milling time is 1 to 3 h. 2+ Preferably, the iron source in step (3) is at least one of ferroferric oxide, iron hydroxide, ferrous oxalate, and ferric oxide; the ratio of the molar amount of the iron source to the molar amount of the manganese source is 5:5 to 1:9; the carboxyl carbon source is at least one of citric acid, tannic acid, fumaric acid, tartaric acid, maleic acid, ascorbic acid, polyacrylic acid, and ethylenediaminetetraacetic acid; the addition amount of the carboxyl carbon source is 1% to 5% relative to the mass of the product; the reaction time is 0.2 to 1 h; in the ball milling reaction, the ball milling speed is 300 to 500 r / min, and the ball milling time is 1 to 3 h.

[0011] Preferably, the iron source in step (3) is at least one of ferroferric oxide, iron hydroxide, ferrous oxalate, and ferric oxide; the ratio of the molar amount of the iron source to the molar amount of the manganese source is 5:5 to 1:9; the carboxyl carbon source is at least one of citric acid, tannic acid, fumaric acid, tartaric acid, maleic acid, ascorbic acid, polyacrylic acid, and ethylenediaminetetraacetic acid; the addition amount of the carboxyl carbon source is 1% to 5% relative to the mass of the product; the reaction time is 0.2 to 1 h; in the ball milling reaction, the ball milling speed is 300 to 500 r / min, and the ball milling time is 1 to 3 h.

[0012] Preferably, the ratio of the total molar amount of lithium ions to transition metal ions in step (4) is 1.00 to 1.08:1; the second organic carbon source is at least one of glucose, sucrose, starch, polyvinyl alcohol, polyethylene glycol, β-cyclodextrin, and polyvinylpyrrolidone; the total mass of the organic carbon source is 5% to 10% relative to the mass of the product; the atmosphere is at least one of nitrogen, argon, argon-hydrogen, and hydrogen; the sintering temperature is 500 to 750℃, and the sintering time is 4 to 12 h; preferably, the ratio of the total molar amount of lithium ions to transition metal ions is 1.02 to 1.05:1; the sintering temperature is 600 to 750℃; and the sintering time is 4 to 10 h.

[0013] Preferably, the conductive agent in step (5) can be at least one of materials known in the lithium battery field, such as acetylene black, Super-P, and CNT; the binder can be at least one of materials known in the lithium battery field, such as PVdF, PVA, and PTFE; the baking time is 4 to 24 h; preferably, in the positive electrode material, the weight percentage content of the conductive agent is 1% to 15%, the weight percentage content of the binder is 1% to 15%, and the balance is the positive electrode material; and the baking time is 4 to 10 h.

[0014] Compared with the prior art, the present application has the following beneficial effects: The present application uses lithium phosphate as a lithium source, instead of lithium carbonate which is more expensive. Since lithium phosphate contains phosphorus elements, the overall material cost can be reduced. In addition, during the preparation of lithium manganese iron phosphate, the particle size is usually ground finer, which faces the problem of sharp increase in slurry viscosity. By introducing lithium phosphate instead of lithium carbonate, and combining the auxiliary role of carboxyl carbon source, the carboxyl carbon source has abundant carboxyl groups, which can enhance the adsorption capacity of the carbon source to the surface of manganese iron oxide, effectively reduce the viscosity of the reaction system, and improve the fluidity of the slurry, so as to obtain a high solid content of phosphorus manganese iron lithium slurry with uniform distribution of elements, so as to prepare high-performance lithium manganese iron phosphate cathode material, thereby realizing the optimization of the reaction process and the reduction of production cost. BRIEF DESCRIPTION OF DRAWINGS

[0015] Figure 1 SEM image of the lithium manganese phosphate precursor prepared in Example 1; Figure 2 SEM image of the lithium manganese iron phosphate cathode material prepared in Example 2; Figure 3 Charge-discharge curve of the lithium manganese iron phosphate cathode material prepared in Example 3; Figure 4 Cycle performance of the lithium manganese iron phosphate cathode material prepared in Example 3; Figure 5 XRD pattern of the lithium manganese iron phosphate cathode material prepared in Example 4; Figure 6 SEM image of the lithium manganese iron salt precursor prepared in Comparative Example 1; Figure 7 Cycle performance of the lithium manganese iron phosphate cathode material prepared in Comparative Example 2. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical scheme and advantages of the present application clearer, the following will be further described in detail in combination with examples. It should be understood that the specific examples described herein are only used to explain the present application, and are not used to limit the present application.

[0017] Example 1 In order to make the purpose, technical scheme and advantages of the present application clearer, the following will be further described in detail in combination with examples. It should be understood that the specific examples described herein are only used to explain the present application, and are not used to limit the present application.

[0018] Example 1 Step (1): 0.06 mol of trimanganese tetraoxide and 40 g of deionized water were weighed and added to a reaction container for sufficient stirring reaction to obtain a uniform mixed slurry; Step (2): 0.2 mol of 85% phosphoric acid and 10.2 g of 30% hydrogen peroxide were weighed and mixed uniformly, and then slowly pumped into the system described in step (1), and stirred at 25°C for 0.5 h; the reacted slurry was transferred to a ball mill tank, and ball-milled at a speed of 400 r / min for 1.5 h to obtain a manganese phosphate slurry; Step (3): 0.12 mol of iron hydroxyl oxide was added to the manganese phosphate slurry described in step (2), and after being stirred thoroughly, 1.7 g of fumaric acid was added and reacted for 20 minutes; then the ball-milling reaction was continued for 1 h to ensure uniform mixing of the slurry; Step (4): 0.101 mol of lithium phosphate, 6% of β-cyclodextrin relative to the mass of the product, and 2% of PEG were added to the slurry obtained in step (3), and mixed uniformly, then ball-milled for 3 h, and then the slurry was transferred to a horizontal sand mill and sand-milled until the particle size D50 of the slurry was 0.32 μm, to obtain a lithium manganese iron phosphate precursor; the precursor was sintered at 650°C for 6 h under high-purity argon to prepare a lithium manganese iron phosphate positive electrode material with excellent performance; Step (5): The lithium manganese iron phosphate positive electrode material obtained in step (4) was uniformly mixed with a certain amount of conductive agent and binder, N-methyl pyrrolidone was used as the solvent, and the mixture was ground into a uniform slurry, coated on an aluminum foil, and placed in a 120°C vacuum oven for a certain period of time; the obtained electrode piece was punched into a 14 mm round piece on a mold, and assembled into a button-type half-cell in an inert glove box for electrochemical performance testing; Example 2 Compared with Example 1, only 0.06 mol of Mn3O4 was replaced by 0.18 mol of electrolytic manganese dioxide, the amount of hydrogen peroxide was changed to 30.6 g, and the others remained unchanged.

[0019] Example 3 Compared with Example 1, only the iron source was replaced with ferrous oxalate, and the others remained unchanged.

[0020] Example 4 Compared with Example 1, the manganese-iron ratio in the prepared lithium manganese iron phosphate was adjusted from 6:4 to 7:3, and the specific implementation content was as follows: Step (1): 0.07 mol of trimanganese tetraoxide and 50 g of deionized water were weighed and added to a reaction container for thorough stirring to obtain a uniformly mixed slurry; Step (2): 0.2 mol of 85% phosphoric acid and 12 g of 30% hydrogen peroxide were weighed and mixed uniformly, and then slowly pumped into the system described in step (1), and stirred at 25°C for 0.5 h; the reacted slurry was transferred to a ball mill tank, and ball-milled at a speed of 400 r / min for 2 h to obtain a manganese phosphate slurry; Step (3): 0.09 mol of ferrous oxalate was added to the manganese phosphate slurry of step (2), and after stirring thoroughly, 1.3 g of polyacrylic acid was added and reacted for 20 minutes; then the ball milling reaction was continued for 1 h to ensure uniform mixing of the slurry; Step (4): 0.101 mol of lithium phosphate, 8% of starch and 2% of PEG relative to the mass of the product were added to the slurry obtained in step (3), and after mixing uniformly, the slurry was ball milled for 3 h, and then the slurry was transferred to a horizontal sand mill and sand milled until the particle size D50 of the slurry was 0.3 μm, thereby obtaining a lithium manganese iron phosphate precursor; the precursor was sintered at 670℃ for 8 h under high-purity argon to prepare a lithium manganese iron phosphate positive electrode material with excellent performance; Step (5): The lithium manganese iron phosphate positive electrode material obtained in step (4) was uniformly mixed with a certain mass of conductive agent and binder, N-methyl pyrrolidone was used as the solvent, and the mixture was ground into a uniform slurry, coated on an aluminum foil, and placed in a 120℃ vacuum oven for a certain period of time; the obtained electrode sheet was punched into a 14 mm round sheet on a mold, assembled into a button half-cell in an inert glove box, and subjected to electrochemical performance testing; Comparative Example 1 Compared with Example 1, only the iron source was added and reacted directly, without adding a carboxyl carbon source, and the others were unchanged.

[0021] Comparative Example 2 Compared with Example 1, lithium phosphate was replaced with lithium carbonate, and the specific implementation was as follows.

[0022] Step (1): 0.06 mol of trimanganese tetraoxide and 40 g of deionized water were weighed and added to a reaction container for thorough stirring and reaction, obtaining a uniformly mixed slurry; Step (2): 0.3 mol of 85% phosphoric acid and 10.2 g of 30% hydrogen peroxide were weighed and mixed uniformly, and then slowly pumped into the system described in step (1), and stirred at 25℃ for 0.5 h; the reacted slurry was transferred to a ball mill tank and ball milled at a speed of 400 r / min for 1.5 h, thereby obtaining a manganese phosphate slurry; Step (3): 0.12 mol of iron hydroxyl oxide was added to the manganese phosphate slurry of step (2), and after stirring thoroughly, 1.7 g of fumaric acid was added and reacted for 20 minutes; then the ball milling reaction was continued for 1 h to ensure uniform mixing of the slurry; Step (4): 0.1015 mol of lithium carbonate, 6% of β-cyclodextrin and 2% of PEG relative to the mass of the product were added to the slurry obtained in step (3), and the mixture was uniformly mixed and ball milled for 3 h, and then the slurry was transferred to a horizontal sand mill and sand milled until the particle size D50 of the slurry was 0.33 μm, to obtain a lithium iron manganese phosphate precursor; the precursor was sintered at 650°C for 6 h under high-purity argon, to prepare a lithium iron manganese phosphate positive electrode material with excellent performance; Step (5): the lithium iron manganese phosphate positive electrode material obtained in step (4) was uniformly mixed with a certain amount of conductive agent and binder, N-methyl pyrrolidone was used as a solvent, and the mixture was ground into a uniform slurry, coated on an aluminum foil, and placed in a vacuum oven at 120°C for a certain period of time; the obtained electrode sheet was punched into a 14 mm round sheet on a mold, assembled into a button-type half cell in an inert glove box, and subjected to electrochemical performance testing.

[0023] Table 1 Comparison of solid content and viscosity of examples and comparative examples

[0024] Although the embodiments of the present application have been described, those skilled in the art can make various changes, modifications, replacements or modifications to the embodiments without departing from the principles and spirits of the present application; the protection scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A low cost method for the preparation of lithium ion battery cathode material lithium manganese iron phosphate, characterized by, The manganese oxide is pre-reacted with phosphoric acid and hydrogen peroxide to obtain a manganese phosphate slurry; then an iron source and a carboxyl carbon source are added to the reaction system, and after being stirred and mixed uniformly, the mixture is ball milled for a period of time; then lithium phosphate and an organic carbon source are added to the reaction container, and the raw materials are fully mixed and refined; finally, the obtained slurry is spray dried and sintered at high temperature to obtain a lithium manganese iron phosphate positive electrode material, comprising the following steps: Step (1): a certain amount of manganese oxide and deionized water are weighed and added to a reaction container and stirred to obtain a uniform slurry; Step (2): a certain amount of phosphoric acid and hydrogen peroxide are weighed and mixed uniformly, and then pumped into the slurry of step (1) at a certain temperature and stirred for a certain period of time; the reacted slurry is transferred to a ball mill tank for further ball milling for a certain period of time to obtain a manganese phosphate slurry; Step (3): a certain amount of iron source is added to the slurry obtained in step (2), stirred uniformly, and then a carboxyl carbon source is added and reacted for a certain period of time; further ball milling is continued for a certain period of time to ensure uniform reaction of the slurry; Step (4): the slurry obtained in step (3) is ball milled and sand milled with a certain proportion of lithium phosphate and a second carbon source, and then spray dried to obtain a lithium manganese iron phosphate precursor; the precursor is sintered at a specific atmosphere and temperature for a certain period of time to obtain a lithium manganese iron phosphate positive electrode material with excellent performance; Step (5): the lithium manganese iron phosphate positive electrode material obtained in step (4) is mixed with a certain amount of conductive agent and binder to form a uniform slurry with N-methyl pyrrolidone as the solvent, and then coated on an aluminum foil and dried in a vacuum oven at 120°C; the obtained electrode piece is punched into a 14 mm round piece, and assembled into a button-type half cell in an inert atmosphere glove box for electrochemical performance test.

2. The low cost preparation method of lithium ion battery cathode material lithium iron manganese phosphate according to claim 1, characterized in that: The manganese oxide of step (1) is at least one of trimanganese tetraoxide, manganese dioxide and manganous oxide; the deionized water has a mass of 1-5 times that of the manganese source.

3. The low cost preparation method of lithium ion battery cathode material lithium manganese iron phosphate according to claim 1, characterized in that: The phosphoric acid concentration of the step (2) is 60%~85%, the phosphoric acid molar quantity is (total transition metal ion molar quantity minus the molar quantity of phosphorus in the lithium source); the hydrogen peroxide concentration is 25%~35%, the hydrogen peroxide molar quantity is 1.2~2 times of the manganese ion Mn 2+ in the theoretical reduced manganese source, and the reaction time is 0.2~1h; in the ball milling reaction, the ball milling rotation speed is 300~500r / min, and the ball milling time is 1~3h.

4. The low cost preparation method of lithium ion battery cathode material lithium iron manganese phosphate according to claim 1, characterized in that: The iron source of step (3) is at least one of triiron tetroxide, iron hydroxide, ferrous oxalate and diiron trioxide; the molar ratio of the iron source to the manganese source is 5:5-1:9; the carboxyl carbon source is at least one of citric acid, tannic acid, fumaric acid, tartaric acid, maleic acid, ascorbic acid, polyacrylic acid and ethylenediaminetetraacetic acid; the addition amount of the carboxyl carbon source is 1-5% relative to the mass of the product; the reaction time is 0.2-1h; in the ball milling reaction, the ball milling speed is 300-500r / min, and the ball milling time is 1-3h.

5. The low cost preparation method of lithium ion battery cathode material lithium manganese iron phosphate according to claim 1, characterized in that: The ratio of total moles of lithium ions to transition metal ions in step (4) is 1.00-1.08:1; the second organic carbon source is at least one of glucose, sucrose, starch, polyvinyl alcohol, polyethylene glycol, β-cyclodextrin, and polyvinylpyrrolidone; the total mass of the organic carbon source is 5-10% relative to the mass of the product; the atmosphere is at least one of nitrogen, argon, argon-hydrogen, and hydrogen; the sintering temperature is 500-750°C, and the sintering time is 4-12 h; preferably, the ratio of total moles of lithium ions to transition metal ions is 1.02-1.05:1; the sintering temperature is 600-750°C; and the sintering time is 4-10 h.

6. The low cost preparation method of lithium ion battery cathode material lithium manganese iron phosphate according to claim 5, characterized in that: The conductive agent in step (5) can be at least one of acetylene black, Super-P, and CNT, which are known in the lithium battery field; the binder can be at least one of PVdF, PVA, and PTFE, which are known in the lithium battery field; the baking time is 4-24 h; preferably, in the positive electrode material, the weight percentage content of the conductive agent is 1-15%, the weight percentage content of the binder is 1-15%, and the remainder is the positive electrode material; and the baking time is 4-10 h.

Citation Information

Cited By

  • Ultralow-viscosity lithium manganese iron phosphate material and preparation method thereof

    CN121536900A